2013
DOI: 10.1002/jtr.1961
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Conservation Aptitude of Surf Beaches in Phuket, Thailand: An Application of the Surf Resource Sustainability Index

Abstract: The research seeks to measure the conservation aptitude of nine surf beaches in Phuket, Thailand by employing the Surf Resource Sustainability Index, an assessment methodology comprising 27 social, economic, environmental and governance indicators used to frame and quantify attributes for conservation development. The research identifies and documents key areas of concern for the sustainability of the island's coastal surfing resources and distinguishes steps forward to address emergent issues. The study finds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…Case studies were carried out in Phuket, Thailand (Martin, 2013a(Martin, , 2013bMartin & Assenov, 2012b, 2013a, 2013c. The trials found that considerable time and experience is required to attach quantitative values to qualitative attributes, yet the process served to catalogue and measure sustainability factors with two significant implications.…”
Section: Previous Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Case studies were carried out in Phuket, Thailand (Martin, 2013a(Martin, , 2013bMartin & Assenov, 2012b, 2013a, 2013c. The trials found that considerable time and experience is required to attach quantitative values to qualitative attributes, yet the process served to catalogue and measure sustainability factors with two significant implications.…”
Section: Previous Applicationsmentioning
confidence: 99%
“…To address these concerns and the protection and management of coastal surfing resources, the SRSI was developed. The SRSI provides a framework of sustainability indicators used in the assessment of a surf site's aptitude for conservation management based on the premise that the sustainability and conservation of resources can be fostered through a metric-orientated planning and development methodology (Martin & Assenov, 2012b, 2013a, 2013c. As a modular approach to surf site field assessment, SRSI provides a set of building blocks which include qualitative and quantitative metrics.…”
Section: The Surf Resource Sustainability Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…Key areas of Thai tourism research include ecotourism, agrotourism, community-based tourism (CBT), the sustainability of coastal resources, and the impacts of tourism on people, place and economy. For example, recent studies on Phuket's surf tourism industry examine coastal resources through a geographic lens (Martin, 2010(Martin, a, b, c, 2013Martin & Assenov, 2015;Martin & Ritchie, 2018b). Travel guides aimed at the public often refer to physical features and human characteristics of Thai geography and are therefore relevant to the field.…”
Section: Tourism Geography and Geotourismmentioning
confidence: 99%
“…Dicha revisión, que se ha visto apoyada también por otros análisis bibliográficos existentes a nivel internacional (Martin y Assenov, 2011y 2012Scarfe, Healy y Rennie, 2009a), arroja también un escaso conocimiento, tanto a nivel teórico como de estudios de casos, sobre las cuestiones abordadas en este trabajo, particularmente en lo referido a los hábitos y motivaciones de los surfistas y los factores de mayor atracción de los destinos de práctica, pese a su importancia por las acciones de marketing y planificación de los agentes turísticos y organizaciones que promueven el turismo de surf (Barbieri y Sotomayor, 2013). Y lo mismo ocurre con otras tan importantes como el análisis y valoración de los condicionamientos e implicaciones territoriales de las prácticas turístico-deportivas surfistas, pese a resultar fundamentales para estudiar sus perspectivas de sostenibilidad.…”
Section: Introducción Y Marco Teóricounclassified